2013
DOI: 10.1111/codi.12186
|View full text |Cite
|
Sign up to set email alerts
|

The impact of anorectal malformations on anorectal function and social integration in adulthood: report from a national database

Abstract: Anorectal malformation ARM often leads to suboptimal bowel function in adulthood. This has an impact on social integration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 12 publications
0
22
0
1
Order By: Relevance
“…[13][14][15][16][17][18][19][20][21][22][23][24] there were no published randomized clinical trials on the topic. there was 1 prospective controlled study, 13 1 retrospective cohort study, 14 and 10 cross-sectional survey studies [15][16][17][18][19][20][21][22][23][24] (table 1). the studies were conducted at a broad range of medical and surgical centers in sweden, 13 singapore, 14 Germany, 15 14,17,18,20 seven studies, with a total of 308 patients, analyzed the prevalence of chronic constipation, which ranged from 22.2% to 86.7%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16][17][18][19][20][21][22][23][24] there were no published randomized clinical trials on the topic. there was 1 prospective controlled study, 13 1 retrospective cohort study, 14 and 10 cross-sectional survey studies [15][16][17][18][19][20][21][22][23][24] (table 1). the studies were conducted at a broad range of medical and surgical centers in sweden, 13 singapore, 14 Germany, 15 14,17,18,20 seven studies, with a total of 308 patients, analyzed the prevalence of chronic constipation, which ranged from 22.2% to 86.7%.…”
Section: Resultsmentioning
confidence: 99%
“…there was 1 prospective controlled study, 13 1 retrospective cohort study, 14 and 10 cross-sectional survey studies [15][16][17][18][19][20][21][22][23][24] (table 1). the studies were conducted at a broad range of medical and surgical centers in sweden, 13 singapore, 14 Germany, 15 14,17,18,20 seven studies, with a total of 308 patients, analyzed the prevalence of chronic constipation, which ranged from 22.2% to 86.7%. 13,14,17,[20][21][22]24 the largest study (n = 59) reported a prevalence of 33.9% (95% Ci, 23.0%-46.8%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, FI frequently persists in adulthood[1]. Adult colorectal surgeons do not see these patients very often, as follow-up may not be recommended by pediatric surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeries in the first years of life for imperforate anus can lead to lifelong problems with fecal incontinence (FI) with a great impact on quality of life[1], largely due to the neo-anus in relation to the anal sphincter position and integrity. Despite successful surgery, results for fecal continence and quality of life can be disappointing.…”
Section: Introductionmentioning
confidence: 99%